Could infantile interactive drawing technique be useful to promote the communication between children with Type-1 diabetes and pediatric team? - Vanelli, Maurizio; Munari, Alberto; Fabbri, Donata; Iovane, Brunella; Scarabello, Chiara; Dodi, Icilio; Mastrorilli, Carla; Fainardi, Valentina; Di Mauro, Dora; Caffarelli, Carlo (Acta Biomedica Atenei Parmensis, 2018)
Aim: to finding what young patients with type-1 diabetes (T1D) knows about their body and also on their illness in perspective to tailor educational interventions to their real ability to understand. Methods: the present study involved 68 children with T1D , 5 to 14 years old with a duration of diabetes ranging from 2 to 6 years and a total HbA1c mean value of 7.96±0.87%. The sample was divided into two age Groups: 28 children 5 to 10 years old were gathered in the Group 1 and 40 teenagers aged from 11 to 14 years in the Group 2. These patients were invited to draw over a white paper using a black pencil “The human body as it is made inside”. Subsequently they were asked to explain: “what is diabetes?” and “where does insulin go?”. According to the methodology of the “interactive drawing”, the interviewer interacted with the children while drawing, forcing them to verbalize the reasons for their choices, to justify their proceeding, to explain their plan and then to explicit their theories. Drawings and replies were classified as Correct, Correct-but-Incomplete and Incorrect. Results: the overall production of correct/correct-but-incomplete drawings was 83.82% vs 16.20% of the incorrect ones. One-hundred of the children who have produced a correct drawing supplied also a correct verbal reply, whereas 100% of the children who have produced an incorrect drawing was unable to supply any information on diabetes or about insulin. Both younger and older subjects who produced a complete-but-incorrect drawing appeared to have misunderstood the action of insulin therapy (only 23% and 17% of correct replies). Children who produced incomplete drawings and provided incorrect replies to the questions about their disease showed also a HbA1c mean value higher (8.36±0.97%) compared to the children who drew and answered correctly (p=0.0023). Conclusions: the operative epistemic approach could represent a promising tool for a health professional team to verify the real understanding acquired by a child about T1D, and to provide pediatrician a guideline to directly communicate with his patient.